Keputusan investasi, kebijakan utang, dan kebijakan dividen pada nilai perusahaan - Valen Winda; Marcellia Susan (Universitas Kristen Maranatha, 2022)
This study analyzes the influence (both simultaneously and partially) of investment decisions, debt policies, and dividend policies on firm value in the food and beverage sub-sector manufacturing companies listed on the Indonesia Stock Exchange in 2017-2020. This research also confirms the determinants of firm value which is not supports to previous studies. This research uses an explanatory research method. The population in this study is the food and beverage sub-sector companies listed on the Indonesia Stock Exchange in 2017-2020, totaling 21 companies. The sample was nine companies using non-probability sampling with a purposive sampling method. The data analysis in this study is a panel data regression analysis with the random effect method. The results showed that investment decisions positively influence firm value. Debt policy and dividend policy negatively impact firm value. The study results prove that investment decisions, debt policies, and dividend policies simultaneously affect firms value by 18.63 percent. Investment decisions can determine the value of the company. The company, which analyzes and makes decisions with sound judgment, will grow and generate high profits so that investors are interested in investing in the company and will increase the value of the company.